2021
DOI: 10.21203/rs.3.rs-1193371/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of the Angular Gyrus in Semantic Cognition – A Synthesis of Five Functional Neuroimaging Studies

Abstract: Semantic knowledge is central to human cognition. The angular gyrus (AG) is widely considered a key brain region for semantic cognition. However, the role of the AG in semantic processing is controversial. Key controversies concern response polarity (activation vs. deactivation) and its relation to task difficulty, lateralization (left vs. right AG), and functional-anatomical subdivision (PGa vs. PGp subregions). Here, we combined the fMRI data of five studies on semantic processing (n = 172) and analyzed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Third, control regions are expected to show stronger activation for harder tasks (Noonan et al, 2013). In contrast, a recent large-scale fMRI study (N = 172) revealed that multimodal IPL shows the opposite relationship: lower activity for harder tasks (Kuhnke et al, 2022). Moreover, left IPL was not engaged in a recent meta-analysis of “semantic control”—the controlled retrieval of conceptual information (Jackson, 2021).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Third, control regions are expected to show stronger activation for harder tasks (Noonan et al, 2013). In contrast, a recent large-scale fMRI study (N = 172) revealed that multimodal IPL shows the opposite relationship: lower activity for harder tasks (Kuhnke et al, 2022). Moreover, left IPL was not engaged in a recent meta-analysis of “semantic control”—the controlled retrieval of conceptual information (Jackson, 2021).…”
Section: Discussionmentioning
confidence: 82%
“…In contrast to the “amodal” ATL, “multimodal” hubs like left IPL and pMTG retain modality-specific perceptual-motor information about the individual modalities that they bind (Fernandino et al, 2016b; Kuhnke et al, 2022, 2021, 2020b; Reilly et al, 2016b; Seghier, 2013). Hence, these regions are sensitive to modality-specific conceptual information related to several modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation